PENDEKATAN LEAN MANUFACTURING UNTUK MENGURANGI LEAD TIME PADA PROSES TREATMENT MOLTEN STEEL PERUSAHAAN BAJA - Hanan, Siti; Mustofa Zein, Aji; Ramadhania, Sherin (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
This steel manufacturing company located in Citangkil District, Cilegon City is a company engaged in the steel manufacturing industry in Indonesia. Based on research conducted in the period January 2023 to January 2024, it was recorded that there was a swelling of the lead time in the production process in the Rheinstall Heraeus (RH). In this study, the author uses the lean manufacturing method. This method can analyze and determine the activities that need to be done and the activities that do not need to be done, with Vallue added and non value added tools (VA and NVA) after knowing the activities that need to be done and the activities that do not need to be done, then continue with the Value Stream Mapping (VSM) tools to get the value of waste that can be eliminated. The result of the research using the Lean Manufacturing method is that the lead time in the treatment process has been successfully reduced, which originally took up to 1780 seconds to 1520 seconds, and was carried out safely without ignoring the SOP and Safety that apply in the company. The results of the research using the Lean Manufacturing method are, the lead time in the treatment process has been successfully reduced, the waste itself is found in the treatment stage starting from the vacuum start process from 120 seconds to 60 seconds, taking the initial temperature from 120 seconds to 100 seconds, the waiting time of 380 Torr which takes 120 seconds to 60 seconds, Charging the material originally took 80 seconds to 60 seconds, the circulation of the original material took 80 seconds to 60 seconds, the composition taking from 120 seconds to 100 seconds, and in the Torr vacuum stop process which took 120 seconds to 60 seconds. So that it can produce a total time of up to 1780 seconds to 1520 seconds, and it is carried out safely without ignoring the SOPs and Safety that apply in the company.